Helicobacter pylori luxS mutants cause hyperinflammatory responses during chronic infection - Christina Yang; Alessandra Rodriguez y Baena; Bryce A. Manso; Shuai Hu; Raymondo Lopez-Magaña; Mané Ohanyan; Karen M. Ottemann (Microbiology Spectrum)
ABSTRACT Helicobacter pylori infects roughly half the world’s population, causing gastritis, peptic ulcers, and gastric cancer in a subset. These pathologies occur in response to a chronic inflammatory state, but it is not fully understood how H. pylori controls this process. We characterized the inflammatory response of H. pylori mutants that cannot produce the quorum sensing molecule autoinducer 2 (AI-2) by deleting the gene for the AI-2 synthase, luxS. Our work shows that H. pylori luxS mutants colonize the stomach normally but recruit high numbers of CD4+ T cells to the stomach during chronic infection. This increase in the number of CD4+ T cells correlated with elevated expression of CXCL9, a chemokine important for T cell recruitment. Together, our results suggest that H. pylori may utilize AI-2 signaling to modulate the inflammatory response during chronic infection.IMPORTANCEMany bacteria signal to each other using quorum sensing signals. One type of signal is called autoinducer 2 (AI-2), which is produced and sensed by the LuxS enzyme found in many bacteria, including the gastric pathogen Helicobacter pylori. H. pylori establishes chronic infections that last for decades and lead to serious disease outcomes. How AI-2 signaling and LuxS contribute to chronic H. pylori infection has not been studied. In this work, we analyzed how loss of H. pylori-created AI-2, via mutation of luxS, affects H. pylori chronic infection. luxS mutants did not have significant colonization defects, similar to their reported phenotype during early infection, but they did have high stomach levels of effector and regulatory T cells and T-cell-recruiting chemokines. These results suggest that H. pylori LuxS may play more of a role in modulating the immune response versus colonization.